O ofício de benzer como produção de conhecimento no município de Tracuateua – PA – Amazônia – Brasil - VILLACORTA, Gisela Macambira (Universidade Federal do Pará, 2021)
The craft of blessing consists of a cultural practice of popular knowledge in the Municipality of Tracuateua/ PA related to religious healing. Besides its intrinsic spiritual aspects, blessing is an important source of knowledge production for that community, despite the devaluation of its practice in relation to scientific knowledge. On regard to this theme, this work aimed, through an ethnographic study, to analyze the epistemology of blessing, from popular knowledge and healing practices, based on the concept of education of attention proposed by Tim Ingold. We seek to report the impacts of the overlapping of scientific knowledge over other knowledge, to identify the reasons for the devaluation of blessing practices and to signal the importance of dialogues between knowledges and the valorization of knowledge, regardless of its origin. From this epistemological analysis, we aim to subsidize public policies for the valorization of knowledge and cultural practices